The origins of multicellularity: a multi-taxon genome initiative. - Ruiz-Trillo, I; Burger, G; Holland, P; King, N; Lang, B; Roger, A; Gray, M (2007)
The emergence of multicellular organisms from single-celled ancestors -- which occurred several times, independently in different branches of the eukaryotic tree -- is one of the most profound evolutionary transitions in the history of life. These events not only radically changed the course of life on Earth but also created new challenges, including the need for cooperation and communication between cells, and the division of labor among different cell types. However, the genetic changes that accompanied the several origins of multicellularity remain elusive. Recently, the National Human Genome Research Institute (NHGRI) endorsed a multi-taxon genome-sequencing initiative that aims to gain insights into how multicellularity first evolved. This initiative (which we have termed UNICORN) will generate extensive genomic data from some of the closest extant unicellular relatives of both animals and fungi. Here, we introduce this initiative and the biological questions that underpin it, summarize the rationale guiding the choice of organisms and discuss the anticipated benefits to the broader scientific community.